Descemet Stripping Automated Endothelial Keratoplasty for Endothelial Dysfunction in Xeroderma Pigmentosum: A Clinicopathological Correlation and Review of Literature. Issue 4 (July 2016) - Vira, Divya; Fernandes, Merle; Mittal, Ruchi
Abstract : Abstract: Xeroderma pigmentosum (XP) mainly affects the ocular surface; however, endothelial damage may also occur. We would like to report changes in the endothelial–Descemet layer and review the literature on similar findings in patients with XP, including the role of Descemet stripping automated endothelial keratoplasty (DSAEK) in the management of a 21-year-old man who presented with nonresolving corneal edema in the right eye after excision biopsy for conjunctival intraepithelial neoplasia. His best-corrected visual acuity (BCVA) was 20/200 in the right eye and 20/20 in the left eye. On general examination, there was patchy hyperpigmentation of the exposed areas of skin suggestive of XP. On examination of the right eye, there was stromal edema involving the exposed half of cornea. The left eye appeared normal. Pachymetry readings were 860 and 600 μm in the right and left eye, respectively. Descemet stripping automated endothelial keratoplasty was performed for endothelial dysfunction and the stripped endothelium, and Descemet membrane (DM) was sent for histopathologic evaluation. Postoperatively, the donor lenticule was well apposed and the overlying stromal edema resolved. The patient achieved a BCVA of 20/30 in the right eye without progression of corneal scarring at 1-year follow-up. In the meanwhile, however, the left eye developed corneal edema. Histopathology revealed gross attenuation of endothelial cells with uniform thickness of the DM. Corneal endothelial dysfunction in XP is amenable to treatment with DSAEK.